Pangola grass as forage for ruminant animals: A review - Kanitta Tikam (2018)
This review focuses on the introduction and investigation of pangola grass as a tropical forage species especially in Thailand. Pangola grass (Digitaria eriantha Steud., synonym D. decumbens) is one of recent examples of grasses that have been successfully introduced to Southeast Asia and is often considered as one of the highest quality tropical grasses popularly grown as pasture. Pangola grass is utilized extensively as grass for animal grazing, hay and silage making. Its crude protein content is commonly in the order of 5 to 14% of dry matter and may exceed 15% of dry matter with young regrowth under high fertilization. It has been documented that the type and number of ruminants receiving pangola grass can determine the success of its use. Results obtained when pangola grass in fresh, hay or silage form was fed to ruminant animals as supplements showed better performances in body weight gain, feed conversion ratio, carcass yield, meat quality, and milk yield and composition. In conclusion, pangola grass is a promising forage and a source of high quality feed for ruminant animals in tropical countries. © 2013 Tikam et al.; licensee Springer.